(untitled) (Entrepreneurship Journal for Finance and Business, 2026)
This research aims to analyze the role of empowerment strategies in achieving creative performance among employees of the General Company for Communications and Information Technology (GCIT), a vital government organization operating in a dynamic technological environment that requires continuous renewal and innovation. The research used the descriptive-analytical approach, and data were collected through a questionnaire distributed to a random sample of 140 employees, from which 137 valid questionnaires were retrieved for statistical analysis. The research focused on studying the impact of four dimensions of empowerment strategies: power, knowledge, information, and rewards, as independent variables, while creative performance represented the dependent variable. SPSS V.26 was used to test the hypotheses and study the impact of variables. The research results showed a significant positive effect for most empowerment dimensions in enhancing employees’ creative performance, with the dimensions "power" and "knowledge" having the greatest impact. In contrast, the effect of "rewards" was low. The results confirmed that empowering employees cognitively and practically and providing a supportive organizational environment positively impact their ability to think creatively and devise new solutions. The study recommends adopting comprehensive empowerment policies within the company, creating a work environment that encourages creativity, and reconsidering incentive systems and information flow to enhance organizational performance and keep pace with the requirements of digital transformation.